"SULTANISTIC REGIME" UNDER THE REIGN OF NICOLAЕ CEAUSESCU (1974-1989) - Sporea, Danijel (Political Review, 2024)
The paper analyzes the rule of Nicolae Ceausescu (Nicolae Ceaușescu), based on the theory of the sultanate regime. Observing his rule, a thesis is put forward about the Gravity center of the regime in which the mentioned president ruled before his overthrow. The cessation of this form of government, that is, its end, is often on the line of confrontation between the outbreak of a revolution and violent overthrow. Such a scenario was seen in Romania in 1989, and the common denominator of numerous analyses of Ceausescu’s fall is the characterization of his regime as an extreme form of patrimonialism called sultanism. Based on the significant research of the theoretical approach to the sultanist regime, the author tries to indicate the presence of totalitarian elements in Ceausescu’s system of government, including the circumstances of the transformation of such a regime into sultanism, resistant to all sorts of nonviolent abandonment, except repression. Taking into account the broader theory that the end of some regimes can produce a certain type of political outcome, we are inclined to conclude that certain types of regimes, such as sultanist ones, can generate situations suitable for the outbreak of revolution, which forms the basis of this paper.